PERSONALIZED MARKETING SEBAGAI UPAYA MENCIPTAKAN KEUNGGULAN BERSAING PERUSAHAAN - Santoso, Okky Chandra (Kajian Ilmiah Mahasiswa Manajemen, 2013)
The rapid growth in the business and increasingly tight competition, demanding the company to be competitive with other similar companies. One of them is through personalized marketing. Personalized marketing is a strategy of CRM (Customer Relationship Management) that is based on a personal characteristic of the measuring point of the customer interaction brand with customers. The goal is to increase customer loyalty and ultimately also affect sales. Therefore authors interested in writing more about the implementation of the strategy of personalized marketing in creating competitive advantage for the company. There are a few main reasons why companies do personalization products, namely: 1) allows companies to increase request.; 2) allows companies to get a surplus of infra marginal customers.; 3) Create brand identity; 4) a wide range of customer benefits requirements satisfy their needs and their expectations. Personalization and customization can be a source of competitive advantage for companies especially in increasing relationship marketing to achieve Customer loyalty. The challenge faced by the company in marketing customization factor is a price. The production process of customization can result in high production costs.